The distributional component of the price of the tax avoidance service - Tatiana Damjanovic (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
The traditional avoidance literature undeservedly neglects tax base distribution as a factor affecting the avoidance price, and generally assumed to be equal to the avoidance cost. In reality, avoidance providers are usually either high-skilled specialists or insiders. The strong collusion thus, naturally seems to be an assumption of the behavior of avoidance providers. Within such a framework, income distribution, which forms an avoidance demand together with tax codes, plays a very essential roll for the outcome of both avoidance price and quantity. My article models an economy with a monopolistic avoidance provider and imperfect information, and illustrates possible consequences of tax base changes. The paper examines the relationship between inequality and a government's ability to collect tax revenue, and also considers the possible outcome of a tax base broadening. Furthermore, it provides an additional explanation for the secession decision.
Keywords: C72; D31; D42; D43; D69; D82; E61; E65; F15; G28; G29; H21; H24; H25; H31; H32; J61; K34; L12; O17; 330; Tax avoidance; optimal taxation; income distribution; endogenous prices; inequality; tax base broadening; secession